The Prevalence and Independent Risk Factors of Significant Tricuspid Regurgitation Jets in Maintenance Hemodialysis Patients With ESRD - Zhang, Ying; Ding, Xiao-Han; Pang, Fang; Zhang, Laiping; Wang, Yiqin; Wang, Weili; Rao, Rongsheng; Bian, Shi-Zhu (Frontiers in Physiology, 2020)
Background and aim Tricuspid regurgitation (TR) is a frequent complication in various cardiovascular diseases. However, few studies have reported the prevalence of TR especially the moderate to severe or significant TR (ms-TR) maintenance dialysis patients. Thus, we aimed to identify the prevalence of ms-TR and its associated factors. Methods A total of 491 maintenance dialysis patients underwent echocardiographic examinations, while a subgroup (n = 283) also received routine blood tests, renal function examinations and electrolyte analysis. We first compared the differences in abovementioned parameters among groups with various TR areas (TRAs). Finally, univariate and adjusted regression were also used to identify factors that were independently associated with ms-TR. Results The incidence of TR jets was 62.6%, which included a mildly increased TRA (47.8%), moderately increased TRA (10.4%) and severely increased TRA (3.5%). Most of the cardiac structures and functional parameters, such as the end-diastolic internal diameters of the left atrium (LA), left ventricle (LVDD), right atrium (RA), right ventricle (RV), left ventricular ejection fraction (LVEF) and fractional shortening (FS), were significantly associated with ms-TR. Among serum ions, only total CO2 (TCO2; r = -0.141, p = 0.047) was negatively correlated with TRA. After adjusted, only Na+ [odds ratio (OR): 0.871 0.888, p =0.048], RA (OR: 1.370, p < 0.001) and FS (OR: 0.887, p < 0.001) were independently associated with ms-TR. Conclusion TR occurs in maintenance hemodialysis patients with ESRD. Na+ FS and RA were independently associated with ms-TR, and these parameters may be potential risk factors/predictors for ms-TR.